2005
DOI: 10.1590/s0021-75572005000500008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e gravidade da asma em adolescentes e sua relação com índice de massa corporal

Abstract: Objective: To investigate the relationship between the increase of body mass index and the prevalence and severity of asthma in adolescents from Santa Maria, in southern Brazil, and surrounding regions. Method:A cross-sectional, observational, population-based study was carried out with 4,010 schoolchildren aged 13 and 14 years, without any gender restrictions, who answered the written questionnaire of the International Study of Asthma and Allergies in Childhood (ISAAC) phase III. Body mass index was used (kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
0
4
0
10
Order By: Relevance
“…Outros trabalhos na literatura analisaram a frequência de indivíduos com asma para cada questão definida como indicadora de maior gravidade. Os poucos estudos que definiram um único critério de gravidade através da associação de respostas às perguntas do ISAAC, como fizemos, encontraram uma frequência de asma "mais grave" variando de 24,7 a 30% 8,16 . No entanto, esses estudos consideraram a presença de mais de quatro exacerbações de asma no último ano como um dos parâmetros de gravidade, o que diferiu do nosso critério.…”
Section: Discussionunclassified
“…Outros trabalhos na literatura analisaram a frequência de indivíduos com asma para cada questão definida como indicadora de maior gravidade. Os poucos estudos que definiram um único critério de gravidade através da associação de respostas às perguntas do ISAAC, como fizemos, encontraram uma frequência de asma "mais grave" variando de 24,7 a 30% 8,16 . No entanto, esses estudos consideraram a presença de mais de quatro exacerbações de asma no último ano como um dos parâmetros de gravidade, o que diferiu do nosso critério.…”
Section: Discussionunclassified
“…Na literatura, é descrito que o sobrepeso/obesidade é um fator de risco para uma maior incidência de asma, principalmente no sexo feminino 22 . De um modo geral, adolescentes asmáticos apresentam sobrepeso mais frequentemente do que controles sadios 23,24 . Kushinir 25 encontrou uma associação positiva entre adolescentes obesos de 13 e 14 anos e sintomas de asma (OR = 1,51; IC95% 1,07-2,13).…”
Section: Discussionunclassified
“…Its worldwide prevalence is 7.2%, and the prevalence observed in the study population (5.6%), using the methods described above, came close to this number. 7,10,13 With increasing prevalence of both obesity and asthma, a possible relationship between them has been hypothesized. The existence of possible genetic, biological and physical mechanisms (like gastroesophageal reflux) or chemical mechanisms (inflammatory substances like tumor necrosis factor alpha, leptin or adiponectin) that are common to asthma and obesity has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…5 Recent studies have attempted to demonstrate an association between obesity and asthma, which is a highly prevalent chronic infl ammatory illness (7.2% of the world's population are asthmatic). [6][7][8][9][10] Some studies have demonstrated that reductions in body mass index (BMI) among patients with asthma improve their pulmonary function, asthma symptoms, morbidity and state of health. 7 BMI has been found to be a signifi cant prognostic factor for atopy and allergic symptoms among teenage girls.…”
Section: Introductionmentioning
confidence: 99%